ONE OF THE TWO LITERARY WORKS OF FEMALE AUTHORS IN GEORGIA - Burchuladze, Khatuna (Journal of Learning on History and Social Sciences, 2024)
General Background: The role of female authors in Georgian literature has been pivotal in reflecting and shaping societal norms and cultural narratives. Despite their significant contributions, many female writers have been historically marginalized, with limited recognition of their literary and feminist endeavors. Specific Background: Prominent Georgian female poets and writers, such as Borena Dedofli, Vominia Beridze, Dominika Eristavi, Ekaterine Gabashvili, and Safo Mgeladze, have produced works that intertwine personal emotions with broader societal issues. Their literary creations, often influenced by folk poetry and romanticism, highlight themes of women's rights, social justice, and national identity, yet many of their works remain underexplored or lost. Knowledge Gap: There is a scarcity of comprehensive studies that examine the collective impact of these female authors on Georgian literature and feminist movements. Additionally, the interplay between their literary output and the socio-political context of their times has not been thoroughly investigated. Aims: This study aims to explore the origins and development of female creativity in Georgian literature, highlighting the contributions of key female authors and their influence on both literary traditions and feminist discourse in Georgia. Results: The research uncovers how these female authors navigated and challenged patriarchal structures through their literary works. It highlights Borena Dedofli’s early poetic expressions, Dominika Eristavi’s pioneering feminist writings, and Safo Mgeladze’s advocacy for women’s rights, demonstrating their resilience and creative prowess despite societal constraints. Novelty: This study uniquely integrates archival materials, personal letters, and literary analyses to provide a nuanced understanding of Georgian female authors' contributions. It sheds light on previously overlooked works and contextualizes their literary achievements within the broader feminist movement. Implications: The findings emphasize the importance of recognizing and preserving the legacy of Georgian female authors in literary studies and feminist history. By highlighting their contributions, the study advocates for greater inclusion of women’s voices in the canon of Georgian literature, inspiring future research and promoting gender equality in literary scholarship.